Influence of motivation on academic learning in high school students - Mendoza-García, María Fernanda (International research journal of management, IT and social sciences, 2025)
Motivation is of utmost importance for students’ academic learning because it constitutes the starting point for learning, creates the drive to act, and makes the acquisition of significant knowledge possible. The research aimed to analyze how motivation influences the academic learning of high school students at the Dr. Gonzalo Abad Grijalva Educational Unit in Chone. The methodology began with a descriptive study with a mixed approach, linking qualitative and quantitative data obtained during the research process through the application of techniques such as surveys and interviews. The population was represented by 112 high school students and 8 tutor teachers from the Dr. Gonzalo Abad Grijalva Educational Unit. The results indicated that 62.5% of students believe that teaching methodology is one of the reasons they lose motivation when they start school. It was concluded that the main factor influencing high school students’ motivation is teaching methodology, as it generates insecurity and fear of subjects. As a result, they don’t pay attention or participate in class, don’t complete their homework in the classroom or at home, and stop socializing with their classmates and teachers.